Analysis of 39 Forensic Clinical Sex Identification Cases after Sex Reassignment Surgery - WU Yu-jiao; ZHOU Yue-qin; SHEN Yi-wen; JIANG Jie-qing (Fayixue Zazhi)
ObjectiveTo analyze the characteristics of forensic clinical sex identification cases after sex reassignment surgery for transsexualism, discuss the main point of forensic clinical sex identification in China based on domestic and foreign sex change policies and related cases, so as to standardize relevant identification.MethodsA total of 39 cases of forensic clinical sex identification were collected from Center for Forensic Science, Shanghai Medical College of Fudan University in recent years, and the ratio of sex, identification time, the location of surgery, secondary sex characteristic and other information were statistically analyzed.ResultsTransgender woman accounted for 97.4% of the cases, and 94.9% of the cases were operated in Thailand. All cases were identified after the sex reassignment surgery, and at least one of the secondary sex characteristics was consistent with the postoperative primary sexual characters. There were only 2 cases in which auxiliary examination was applied.ConclusionForensic clinical sex identification should be based on the principle that the primary and secondary sex characteristics are consistent with the changed sex.